2009
DOI: 10.1111/j.1365-2559.2009.03447.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous fibrohistiocytic tumours – an update

Abstract: The term 'fibrohistiocytic' tumour is a descriptive designation without histogenetic connotation for a group of heterogeneous lesions that share morphological features of histiocytes and fibroblasts on light microscopy. However, over the years it has become apparent that many so-called 'fibrohistiocytic' tumours are largely composed of relatively undifferentiated mesenchymal cells, but can also show areas of myofibroblastic differentiation. This review focuses on the clinical and histological features as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
138
1
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(154 citation statements)
references
References 116 publications
(175 reference statements)
4
138
1
8
Order By: Relevance
“…Morphological variants include cellular, aneurysmal, epithelioid, and atypical types, and clinical manifestations range from benign tumors of the skin, deep soft tissues or skeleton to, rarely, metastasizing tumors. [1][2][3] We recently showed that both cutaneous and deep FH may carry specific gene fusions, in which a membereither PRKCB and PRKCD-of the gene family encoding protein kinase C (PRKC) is juxtaposed with a gene encoding a membrane-associated protein. 4 The pathogenetic mechanism was assumed to involve the uncoupling of the carboxy-terminal kinase domain of the PRKC protein from its regulatory domain, and its ectopic localization through fusion with the amino-terminal part of a membrane-associated protein.…”
mentioning
confidence: 99%
“…Morphological variants include cellular, aneurysmal, epithelioid, and atypical types, and clinical manifestations range from benign tumors of the skin, deep soft tissues or skeleton to, rarely, metastasizing tumors. [1][2][3] We recently showed that both cutaneous and deep FH may carry specific gene fusions, in which a membereither PRKCB and PRKCD-of the gene family encoding protein kinase C (PRKC) is juxtaposed with a gene encoding a membrane-associated protein. 4 The pathogenetic mechanism was assumed to involve the uncoupling of the carboxy-terminal kinase domain of the PRKC protein from its regulatory domain, and its ectopic localization through fusion with the amino-terminal part of a membrane-associated protein.…”
mentioning
confidence: 99%
“…Atypical fibrous histiocytoma has been discussed by Bostjan Luzer and Eduardo Colonje in their review article published in 2010. [18] Thomas Mentzel et al [19] reported in their study published In present study 70% tumours measured 1-3cm in greatest dimensions and on cut surface showed whitish homogenous appearance. All revealed classical microscopy of neurofibroma [20] , schwannoma [2] and, MPNST [21] .…”
Section: Perivascular Tumors (08%)mentioning
confidence: 87%
“…[8] Several DF variants exist and are distinguished by their histopathological characteristics. [8] However, variant characterization is not always clear-cut, as the histologic features of several variants can be present within the same lesion.…”
Section: Discussionmentioning
confidence: 99%